1981
DOI: 10.4050/jahs.26.32
|View full text |Cite
|
Sign up to set email alerts
|

Active Control of the Helicopter Rotor for Vibration Reduction

Abstract: Analytical design studies, simulation, and a series of wind tunnel tests have led to the demonstration of a closed-loop vibration suppression system in the Baeing Vertol V/STOL Wlnd Tunnel. Using small amounts of oscillatory swashplate molion, this active ronlrol system simullsneously suppressed up to 90 percent of the fourper-rev vertical force, pitching moment, and rolling moment of a 3.05 m (10 fool)-diameter, four-bladed hingeless rotor. The system operated successfully in a large number of flight coaditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 1 publication
1
23
0
Order By: Relevance
“…Comparing his results to Ref. [26], Lehmann confirmed that a hingeless rotor with low first torsion eigen frequency would need large control angles at the low speed region. He concluded that the first torsion eigen frequency would dominate the HHC efficiency.…”
Section: /Rev Couldsupporting
confidence: 74%
See 1 more Smart Citation
“…Comparing his results to Ref. [26], Lehmann confirmed that a hingeless rotor with low first torsion eigen frequency would need large control angles at the low speed region. He concluded that the first torsion eigen frequency would dominate the HHC efficiency.…”
Section: /Rev Couldsupporting
confidence: 74%
“…Wind tunnel test results of closed loop HHC for vibration reduction applied to a 4-bladed soft-inplane hingeless model rotor are presented in [26] by SHAW and ALBION. The model rotor was dynamically scaled to an early version of the Model 179 of Boeing Vertol.…”
Section: How It All Started: Hhcmentioning
confidence: 99%
“…These zeros can intrinsically limit the benefits achievable from active control systems, and therefore it is very important to identify them as part of the design of any such control system. in [40] where a continuous time analysis of HHC was carried out for the first time and it was shown that, to first approximation, the classical T -matrix HHC algorithm (see [35])…”
Section: Discussionmentioning
confidence: 99%
“…The development of the active fibre composites (AFC) followed by micro fibre composites (MFC) in more recent years, as a conformable yet authoritative material has shown a great promise for the IBC approach [12]. The magnitude of such authority has been well established from early research in higher harmonic control; Shaw and Albion [13] demonstrated that approximately 3 • of pitch change is needed to effectively dampen vibrations with swashplate actuation. This level of pitch change is often used as a guideline in many analytical and experimental efforts.…”
Section: Introductionmentioning
confidence: 98%